Attenuation of fourier amplitude and pseudo relative velocity spectra due to local earthquakes in the national capital region of India. Issue 116 (January 2019) - Gupta, I.D.; Trifunac, M.D.
Abstract: In this paper we present attenuation of spectral amplitudes of strong earthquake ground motion in the National Capital Region (NCR) of India that surrounds and includes the National Capital Territory (NCT) of Delhi. In this region, because of the small volume of seismogenic zone in the shallow crust and the coincidence of this volume with a network of recording strong-motion stations, it is possible to determine the amplitude attenuation and scaling equations along the wave paths in this well-defined shallow geological environment. Similar to the Northeastern region of India, the basement in the NCR zone also comprises the Precambrian metamorphic rocks of the peninsular shield. The frequency-dependent attenuation function for the NCR is therefore obtained by assuming the applicability of the dependence on magnitude and site-condition parameters for the local earthquakes in Northeast India. The validity of the empirical scaling equations thus developed has been established by comparing the estimates of seismic moment and peak ground displacement from long-period extensions and the estimates of seismic wave energy and peak ground acceleration from short-period extensions of the empirical spectra with the expected theoretical trend or recorded values of the same parameters. The presented scaling relations for Fourier (FS) and pseudo relative velocity (PSV) spectra can be considered to provide a sound basis for macro- and micro-zoning specific to the highly risk-prone Delhi region. Highlights: Attenuation of strong motion from earthquakes in National Capital Region (NCR) in India. Scaling equations for Fourier and PSV Spectra from earthquakes in NCR. Scaling strong motion amplitudes in NCR at epicentral distances less than 100 km. Tests of empirical Fourier and PSV spectra at long periods in terms of seismic moment.